Can I make a wish?: a competition on detecting meteors in images - Lorena, A. C.; Kaster, D. S.; Cerri, R.; Faria, E. R.; Melo, V. V. de (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe); 2018: Anais do VI Symposium on Knowledge Discovery, Mining and LearningDO - 10.5753/kdmile.2018.27389, 2018)
Promoting competitions has become a path towards attracting people’s interest into diverse areas. Many international conferences have sessions dedicated to one or more competitions, in which participants are challenged by real problems for which advanced solutions are needed. This paper describes the first Brazilian competition on Knowledge Discovery in Databases (KDD-BR), which was part of three main events of the Brazilian Computer Society dedicated to Artificial Intelligence, Databases and Data Mining. In this first edition the participants were supposed to detect meteors, popularly known as shooting stars, in regions of interest of images collected from a monitoring station located at São José dos Campos, Brazil. The data set assembled is detailed, which may be of interest for future benchmark studies using such data. The competition results, contributions and limitations are also discussed, providing a guide for future editions.